EVALUATION OF TWO NESTED PCR-BASED DIAGNOSTIC ASSAYS FOR PLASMODIUM FALCIPARUM INFECTION - Kritsiriwuthinan, Kanyanan; Choosang, Kanthima; Sunantaraporn, Sakone (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: The majority of malaria cases and deaths are caused by Plasmodium falciparum. The rapid and accurate diagnosis is very important for malaria treatment and control. The aim of this study was to evaluate two nested polymerase chain reaction (PCR)-based methods (protocol A and protocol B) for P. falciparum infection, diagnosis in Thailand. Methods: A total of 90 dried blood spot samples were investigated. The samples composed of P. falciparum-, Plasmodium vivax-infected blood and normal human blood samples. The microscopic examination was used as gold standard. Results: The results showed the sensitivity of 100/83.33%, specificity of 100/100%, and accuracy of 100/94.44% for protocol A and protocol B, respectively. The analytical sensitivity of protocol A and protocol B was 0.625 and 6.25 parasites/Î¼l, respectively. The comparison among microscopic examination, protocol A and protocol B by statistical analysis, found that they were not a significant difference. The agreements between each method were good. The kappa value between protocol A and protocol B was 0.87, protocol A and microscopy was 1.00, and protocol B and microscopy was 0.87. Conclusion: The results demonstrated that protocol A should be used for further development of P. falciparum diagnosis in Thailand, especially in case of low parasitemia such as asymptomatic infection and for screening blood donors.